Air‐Cathode with 3D Multiphase Electrocatalyst Interface Design for High‐Efficiency and Durable Rechargeable Zinc–Air Batteries. Issue 5 (9th March 2021) - Askari, Sadegh; Mariotti, Davide; McGlynn, Ruairi; Benedikt, Jan
Abstract : The development of rechargeable zinc–air batteries is hindered by the low energy‐conversion efficiency and the short cycle life, which are partly due to the unsatisfactory performance of the oxygen electrocatalysts on the air‐cathode. The low performance of the catalysts is partially due to the complexity of the gas‐involving multiphase interface required for the oxygen catalysis reactions, and it is often acquired only for a fraction of the loaded catalyst that is in direct contact with the 2D surface of the gas diffusion layer (GDL). A paradigm is proposed for extending the active region using an enhanced 3D multiphase interface on the cathode, which comprises abundant active sites with optimized hydrophobicity and reliable stability. The oxygen reduction reaction (ORR) or the bifunctional catalyst is embedded into the bulk of the GDL and forms a semihydrophobic catalyst layer (SCL), whereas an auxiliary hydrophilic oxygen evolution reaction (OER) catalyst layer integrated onto the GDL assists to reduce the polarization during the cell charging and improves the cathode durability. An air‐cathode comprising the SCL exhibits an overall performance superior to the conventional cathode counterparts including cathodes with metal‐based catalysts, due to the enhanced and optimized multiphase interface on the cathode. Abstract : The performance of metal–air batteries is influenced by the design of the catalyst multiphase interface on the air‐cathode. A paradigm is proposed for extending the active catalyst region using an enhanced 3D multiphase interface on the cathode. This interface engineering significantly boosts the performance of a zinc–air battery in terms of power density, energy efficiency, and cycle life.